Changes in emulsifying properties of caseinate–Soy soluble polysaccharides conjugates by ultrasonication - Sedighe Tavasoli; Yahya Maghsoudlou; Hoda Shahiri Tabarestani; Seid Mahdi Jafari (Ultrasonics Sonochemistry, 2023)
This research aimed to assess the impact of ultrasonication on the emulsifying ability of a conjugate system composed of sodium caseinate and soluble soy polysaccharides. The study analyzed the characteristics of the particles and evaluated the emulsions produced using nanoconjugates. The results showed that ultrasonication improved the contact angle (63.7°) and decreased particle size (75 nm), resulting in more effective emulsifying efficiency. At a 2 % concentration of the nanoconjugates, stable emulsions with a 50 % oil content were successfully formed through complete coverage of the droplets' surface, and no oil release was observed. Moreover, the emulsions’ creaming index remained below 25 % even after 60 days of storage. The stability of the nanoconjugate-based emulsions depended on the concentration of nanoconjugates, with an optimal concentration of 4 %. These findings suggest that the nanoconjugates have great potential as a natural stabilizer for emulsion-based products.